Prevalence of Ectoparasites and Endoparasites in Sacrificial Cattle in the Lubuk Minturun Area, Padang, West Sumatra, Indonesia - Mairawita Mairawita; Putri Afifah Mawaddah; Selviana Oei; Fajri Hidayat; Taufik Rahman (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Cattles hold significant social and religious value in people's lives, especially during the Eid al-Adha celebration, where they are used as sacrificial animals in religious rituals. This study aimed to analyze the prevalence of ectoparasite and endoparasite infections in sacrificial cattles in Lubuk Minturun, Padang City. A total of five cattles were examined, representing three different pen conditions within a single farm, with two cattles selected from each pen as representatives. Methodology: Ectoparasite samples were collected using purposive sampling, while endoparasite samples were obtained using the flotation method. Microscopic examination was conducted for parasite identification. Findings: Two main ectoparasites were identified: Haemaphysalis longicornis and Rhipicephalus microplus. The prevalence of H. longicornis was highest in Cattle I (88.8%), followed by Cattle II (84.8%), Cattle III (68.6%), Cattle IV (59.5%), and Cattle V (65.8%). Meanwhile, R. microplus showed lower prevalence rates: Cattle I (11.2%), Cattle II (15.2%), Cattle III (31.4%), Cattle IV (40.5%), and Cattle V (34.2%). Ectoparasite infestations were most commonly found in the neck region, followed by the ears and buttocks. For endoparasites, Toxocara vitulorum was the most dominant species (63.51%), followed by Ascaris lumbricoides (22.97%), Eimeria sp. (5.40%), Paramphistomum sp. (4.06%), Trichuris sp. (2.70%), and Giardia lamblia (1.36%). These infections can lead to weight loss, digestive disorders, and reduced meat quality, and they may pose zoonotic risks to humans. Contribution: The findings highlight the need for improved livestock management practices, including regular deworming and ectoparasite control, to protect animal health and minimize public health risks